Testing Maze: an educational game for teaching functional testing - Severo, Jan; Lelli, Valéria (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2023: Anais do XXXVII Simpósio Brasileiro de Engenharia de Software, 2023)
Software testing is a fundamental process to increase software reliability. However, teaching software testing using traditional theoretical classes might be discouraging due to the lack of dynamism and practical activities. To solve this problem, methodologies which encourage the students’ participation in a more active way can be used in the classroom. Therefore, from this perspective, approaches involving educational games are increasingly used in undergraduate courses to engage students and facilitate learning. Functional testing is a type of software testing based on the functional requirements of the system, which means a certain functionality is tested without need to access the source code. In this context, this work proposes Testing Maze, an educational puzzle game for teaching functional testing concepts and test specifications containing a fantasy narrative. The game was applied with 31 undergraduate students from the Federal University of Ceará in the Verification, Validation and Software Testing course. The game validation process took place over two stages during two semesters involving 3 different groups of students. In each stage a different version of the game was applied, in the first one a prototype was applied with 14 students and in the second stage a second version of the game containing improvements was applied with 17 students divided into two groups. At the end of each activity, students answered an online questionnaire to evaluate the Testing Maze. At the end of the evaluation, all questionnaire’s questions obtained a majority of favorable responses to the game. Regarding the second version, 14 students considered that Testing Maze helped to understand the concept of functional testing, representing an approval of 82.3% for this version.